ANALISIS KOMODITAS UNGGULAN SUB SEKTOR TANAMAN PANGAN DAN ARAH PENGEMBANGANNYA DI KABUPATEN MIMIKA - Sinta Eka Tandi Payung; Spedy Paraeng (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2020)
This study aims to determine the leading commodities of the food crop sub-sector in Mimika Regency and to determine the direction of the development of the leading commodities of the food crop sub-sector in Mimika Regency. The approach used by researchers is a descriptive approach that aims to describe / describe the leading commodities in the food crops sub-sector and the direction of their development in Mimika Regency. The data collection technique used by researchers is documentation. The analytical tool used in this study is the Location Quotient (LQ) analysis and Differential Shift (DS) analysis in Shift Share Analysis (SSA). Based on the results of the LQ analysis, the leading commodities in Mimika Regency are corn, peanuts, cassava (cassava) and sweet potatoes (petatas). Whereas based on the results of DS analysis, corn commodities are directed at the East Mimika District, Kuala Kencana District and Jita District. Peanut commodities are directed at East Mimika District, Mimika Baru District and Kuala Kencana District. Cassava commodity (kasbi) is directed at West Mimika District, West Mimika District, Far West Mimika District, East Mimika District, Middle East Mimika District, Far East Mimika District, Kuala Kencana District, Agimuga District, Jila District and Jita District. Sweet potato commodity (petatas) is directed at East Mimika District, Kuala Kencana District, Agimuga District and Jila District.